Differential diagnosis of non-traumatic knee hemarthrosis (case report) - A. A. Roskidaylo (Современная ревматология)
Hemarthrosis (HA) of the knee of non-traumatic origin is rarely encountered in the practice of a traumatologist-orthopedic surgeon. The differential diagnosis of this pathology requires a thorough medical history tacking and clinical examination of the patient, and a knee joint aspiration can only confirm the presence of blood in the joint. A diagnostic arthroscopy with a synovial biopsy helps to clarify the diagnosis. The most common causes of non-traumatic HA are tumors of vascular or synovial origin, tumor metastases and the use of high-dose anticoagulants in combination with a vascular malformation.A clinical observation of the development of symptoms of non-traumatic HA on the background of anticoagulant use is presented, where the task of the orthopedic surgeon was to identify the true cause of the disease.